USING EXPERIENCE OF PROFESSIONAL IMPROVEMENT OF POLISH TEACHERS OF SCIENCE AND MATHEMATICS IN POSTGRADUATE PEDAGOGICAL EDUCATION OF UKRAINE (Comparative Professional Pedagogy, 2023)
The article examines the peculiarities of improving the qualifications of Polish teachers as one of the conditions for their professional advancement and obtaining professional degrees. The main tasks of the system of professional improvement of teachers in Poland are characterized – namely, helping young teachers to adapt to the profession, supporting specialists during the period of professional self-affirmation or renewal of the subject, familiarization with the achievements of science, assistance in raising and expanding qualifications. The principles of professional improvement of Polish teachers are defined. They include the relationships between theory and practice, changeability, variety of forms, continuity, multidimensionality, multilevelness and openness. The organizational structure of the system of improving the qualifications of teachers of natural and mathematical subjects in postgraduate education in Poland, which functions at the national, regional, municipal levels, is considered. It is emphasized that the system of improving the qualifications of specialists has a public-state character, is quite variable and flexible; it is created taking into account various needs for continuous professional development and improvement of teachers. Attention is paid to consideration of the forms of professional development of teachers in non-formal education that is aimed at strengthening the internal motivation of specialists, and development of their pedagogical creativity.It is defined that teacher training system in Poland is aimed at the performance of tasks that include professional development, methodical work of teachers, self-education and self-improvement, as well as the implementation of general (educational, developmental, educational, diagnostic) and specific (technological, research, prognostic) functions.Conclusions are made regarding the directions, forms, and content of advanced training of mathematics and science teachers in postgraduate education of the Republic of Poland and the need to form the readiness of Ukrainian specialists to accept European standards in postgraduate pedagogical education.
Keywords: teachers of science and mathematics; professional advancement; development; improvement; advanced training; postgraduate education; experience; Republic of Poland; Ukraine